2021
DOI: 10.3390/molecules26030754
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Antitumor Activity of Indolo[2,3-b] Quinolines, Natural Product Analogs from Neocryptolepine Alkaloid

Abstract: Neocryptolepine (5-methyl-5H-indolo[2,3-b] quinoline) analogs were synthesized and evaluated in vitro and in vivo for their effect versus Ehrlich ascites carcinoma (EAC). The analogs showed stronger cytotoxic activity against EAC cells than the reference drug. The in vivo evaluation of the target compounds against EAC-induced solid tumor in the female albino Swiss mice revealed a remarkable decrease in the tumor volume (TV) and hepatic lipid peroxidation. A noticeable increase of both superoxide dismutase (SOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 46 publications
(25 reference statements)
1
18
0
Order By: Relevance
“…It can cause cell cycle arrest and induce cell apoptosis and has a good antioxidant effect. 23,24,26 However, our study suggested that neocryptolepine lacks potency and has poor selectivity. The cytotoxicity of neocryptolepine to gastric cancer AGS cells was weak, and it was also cytotoxic to normal cells.…”
mentioning
confidence: 66%
“…It can cause cell cycle arrest and induce cell apoptosis and has a good antioxidant effect. 23,24,26 However, our study suggested that neocryptolepine lacks potency and has poor selectivity. The cytotoxicity of neocryptolepine to gastric cancer AGS cells was weak, and it was also cytotoxic to normal cells.…”
mentioning
confidence: 66%
“…Therefore, these analogs may be used to treat many oxidation related diseases such as cancer, cardiovascular, and inflammation caused by oxidative stress (Altwaijry et al, 2021).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Indolobenzazepines and indoloquinolines are fused heterocyclic scaffolds, which have gained a considerable interest in the field of medicinal chemistry. Indolo­[3,2- d ]­benzazepines or paullones (backbone A in Chart ), first synthesized in 1992, were discovered as potential inhibitors of cyclin-dependent kinases (Cdks) ,, with antiproliferative activity similar to that of flavopiridol, the first Cdk-inhibitor that reached clinical trials as an anticancer drug. Later, other possible targets have been identified, namely, sirtuins, , GSK3β, ,,, and mitochondrial malate dehydrogenase .…”
Section: Introductionmentioning
confidence: 99%